Wintertime haze deterioration in Beijing by industrial pollution deduced from trace metal fingerprints and enhanced health risk by heavy metals. (January 2016) - Lin, Yu-Chi; Hsu, Shih-Chieh; Chou, Charles C.-K.; Zhang, Renjian; Wu, Yunfei; Kao, Shuh-Ji; Luo, Li; Huang, Chao-Hao; Lin, Shuen-Hsin; Huang, Yi-Tang
Abstract: Airborne particulate matter (PM) was collected in Beijing between 24 February and 12 March 2014 to investigate chemical characteristics and potential industrial sources of aerosols along with health risk of haze events. Results showed secondary inorganic aerosol was the major contributor to PM2.5 during haze days. Utilizing specific elements, including Fe, La, Tl and As, as fingerprinting tracers, four emission sources, namely iron and steel manufacturing, petroleum refining, cement plant, and coal combustion were explicitly identified; their elevated contributions to PM during haze days were also estimated. The average cancer risk from exposure to inhalable PM toxic metals was 1.53 × 10 −4 on haze days, which is one order of magnitude higher than in other developed cities. These findings suggested heavy industries emit large amounts of not only primary PM but also precursor gas pollutants, leading to secondary aerosol formation and harm to human health during haze days. Highlights: Secondary inorganic aerosol is a major contributor to haze formation in Beijing. Elevated contributions of iron manufacturing, cement plant and petroleum refining to primary PM on haze days are found. The estimated excess cancer risk due to inhalable PM in Beijing is much higher than in other developed cities around the world. Abstract : In this paper, the elevated contributions of iron/steel manufacturing, cement plant and petroleum refining to primary PM on haze days has been quantitatively estimated.